Supramolecular Assemblies for Electronic Materials. Issue 17 (2nd March 2020) - Barendt, Timothy A.; Ball, Melissa L.; Xu, Qizhi; Zhang, Boyuan; Fowler, Brandon; Schattman, Ayden; Ritter, Virginia Cary; Steigerwald, Michael L.; Nuckolls, Colin
Abstract: This work presents a synergy between organic electronics and supramolecular chemistry, in which a host–guest complex is designed to function as an efficacious electronic material. Specifically, the noncovalent recognition of a fullerene, phenyl‐C61 ‐butyric acid methyl ester (PC61 BM ), by an alternating perylene diimide (P )‐bithiophene (B ) conjugated macrocycle (PBPB ) results in a greater than five‐fold enhancement in electron mobility, relative to the macrocycle alone. Characterization and quantification of the binding of fullerenes by host PBPB is provided alongside evidence for intermolecular electronic communication within the host–guest complexes. Abstract : This work reveals a synergy between supramolecular chemistry and molecular electronics. A perylene diimide‐bithiophene conjugated macrocycle is shown to act as a potent receptor for fullerenes, resulting in strong electronic communication between host and guest. When incorporated into the active layer of an organic field effect transistor (OFET) device, these supramolecular complexes enhance electron mobility relative to the empty macrocycle.